THE INFLUENCE OF VARIOUS FACTORS ON LOSS OF ELECTRIC ENERGY IN THE TRACTION NETWORK WHEN THE AC LOCOMOTIVES - Vlasievskyi, S. V.; Klinkova, O. A. (Science and Transport Progress, 2007)
The article is devoted to the impact of the drawbacks of the existing a.c. power supply system on the energy losses in catenary, and to the imperfections of electric energy accounting system.